Case report: heart failure related to intravitreal injection of anti-VEGF - Yuying Sui; Yong Zhao; Nannan Zhou; Haihui Sun; Yuanyuan Sun; Junni Liu; Zunzhe Wang; Jianchun Wang (BMC Cardiovascular Disorders, 2024)
Abstract Background Intravitreal injection of anti-vascular endothelial growth factor is considered the first-line treatment for polypoidal choroidal vasculopathy. It has potential risks for circulatory system, which should be particularly carefully evaluated in older patients. In this case study, we aim to discuss the potential impact of this treatment regimen on cardiac health. Case presentation This case report describes an elderly patient with no prior history of heart disease who exhibited unexpected heart enlargement and dysfunction. Throughout the patient’s hospital stay, various potential causes were investigated, leading to the hypothesis that a 10-year history of intravitreal injections of anti-vascular endothelial growth factor could be related to the observed clinical manifestations. The patient was advised to discontinue this treatment, and after a 2-month follow-up period, there was a gradual improvement in the patient’s cardiac structure and function. Conclusion This manuscript highlights the importance of conducting cardiac examinations before and after anti-vascular endothelial growth factor treatment, especially for individuals at risk of heart diseases like the elderly. It emphasizes the need to carefully weigh the benefits and risks of treatment regimens to ensure optimal therapeutic outcomes.